Imperial Hotel at 308 and 310 Commonwealth Avenue, ca. 1890 - Unknown (Tufts Archival Research Center, 2005)
Street-level view south of the Imperial Hotel, located at 308 and 310 Commonwealth Avenue between Gloucester Street in the east and Hereford Street in the west. The facade of the hotel faces north-northwest towards Commonwealth Avenue. Copyprint 9 1/8 x 7 1/8 Photographs